Kajian Kandungan Logam Berat Pada Sedimen Sungai Di Lokasi Penambangan Emas Tradisional, Desa Boto, Kecamatan Jatiroto - Efendi Putra Dwijaya Pa; Wawan Budianta; Doni Prakasa Eka Putra (Jurusan Teknik Pertambangan, Fakultas Teknik, Universitas Bangka Belitung, 2019)
Traditional and small-scale gold mining, known as ASGM (Small Scale Gold Mining), has been approved forpollution of the environment specifically for watersheds. This research was conducted in Boto Village,Jatiroto Subdistrict, Wonogiri Regency, Central Java Province. This study discusses the analysis ofcomposition and heavy metals and the factors that support heavy metals in the study site. The samplestaken were 22 samples along the river flow in the upstream and downstream areas. Tests of content werenot carried out by the ICP-AES method. Laboratory test results on river sediment samples were thenanalyzed statistically, geoaccumulation index and enrichment factors were calculated. Laboratory test resultsshow that most do not have heavy metal content exceeding the average concentration of heavy metals inriver sediments. The spread of heavy metals in river sediments in the study sites was found to be varied withdifferences in the upstream and downstream areas. In general, upstream areas have higher metal reservescompared to downstream. Distribution of heavy metals for everything that has not been planned, isprocessed by natural processes or human activities. Traditional mining activities contribute significantly incontributing to the addition of Hg, as well as contributing to the increase of other metals, most of which are inthe mineralized area, which fully contains high metal reserves.